PREVENTING NOCTURNAL HEAT TRAPPING IN SEMI-OUTDOOR RETAIL CORRIDORS: RETROFIT HEURISTICS FROM HUMID-TROPICAL FIELD MEASUREMENTS - Aziiz, Akhlish Diinal; Koerniawan, M. Donny; Nugrahenti, Fathina Izmi; Saskia, Cut Sannas; Mabe, Kentaro (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2026)
In humid tropical cities, semi-outdoor retail corridors and promenades support daily activities by providing shade and comfortable walking spaces. However, high ambient humidity and limited nocturnal cooling can reduce the effectiveness after sunset. Thus, 24-hour thermal performance becomes a practical design concern. Objectives: To explain why semi-outdoor retail corridors in humid-tropical areas can remain warmer than adjacent open areas at night. Specifically: (i) quantify the occurrence and magnitude of nocturnal inversion using ΔUTCI/ΔTmrt (node-outdoor); (ii) interpret the patterns using a radiation-ventilation-storage (RVS) framework; and (iii) translate the diagnosis into five retrofit heuristics (H1-H5) for design and operation. Methodology and results: A multi-day field campaign in an Indonesian outlet recorded Ta, RH, and wind speed at outdoor and semi-outdoor nodes every 10 minutes. We derived UTCI and Tmrt, applied quality control, and aggregated the data to hourly medians. At matched timestamps, we computed ΔUTCI and ΔTmrt. During daytime, shaded corridors show clear relief (ΔUTCI < 0, ΔTmrt ≪ 0). At night, deeper under-canopies tend to have smaller Δ and often have a positive Δ, indicating slower post-sunset cooling. More open edges return to outdoor conditions earlier. Conclusion, significance and impact: Five retrofit heuristics are proposed: (H1) Raise local sky exposure; (H2) Split radiative roles; (H3) Enable night-purge paths; (H4) Reduce exposed thermal storage facing pedestrians; and (H5) Deploy vegetation, water, and fans calibrated for humid air. The findings emphasize the need for a day–night design duality—shade by day and release by night—to mitigate nocturnal heat trapping and support safer, more comfortable microclimates in humid tropical retail settings.